The Compare and Contrast of Capital Structure regarding to Large firms and SMEs in the UK - Su, Chao (2011)
ABSTRACT This research attempts to compare and contrast the determinants of capital structure of two data sets: 50 large firms from FTSE 100 and another 50 SMEs (small and medium enterprises) on the FTSE SmallCap Index form the year 2006 to 2010. The proxy of determinants that we use has been suggested by past literatures, including: tangibility, profitability, growth opportunities, firm size, non-debt tax shields and earning volatility. By using the panel data regression model, we have found the correlation between dependent and independent variables. Tangibility, growth opportunities and firm size are the determinants of both two samples while profitability is only significant in the sample of large firms. Non-debt tax shields and earning volatility have no affection on the financing decisions in the UK firms based on our data sets. Although both large firms and SMEs in this country share common determinants of capital structure, there seems to be no clearly linked of their financing decisions. Additionally, the pecking order theory is more applicable to explain the capital structure of all size of firms in the UK.